The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11390-015-1578-2
|View full text |Cite
|
Sign up to set email alerts
|

TagCombine: Recommending Tags to Contents in Software Information Sites

Abstract: Nowadays, software engineers use a variety of online media to search and become informed of new and interesting technologies, and to learn from and help one another. We refer to these kinds of online media which help software engineers improve their performance in software development, maintenance, and test processes as software information sites. In this paper, we propose TagCombine, an automatic tag recommendation method which analyzes objects in software information sites. TagCombine has three different com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
(80 reference statements)
0
14
0
Order By: Relevance
“…Such as code search (e.g., [2,24,31,39]), clone detection (e.g., [7,18,19,64,67]), program repair (e.g,. [10,45,60,66]), document (such as API and questions/answers/tags) recommendation (e.g., [22,25,26,55,63,65,69,70,76]).…”
Section: Machine/deep Learning On Software Engineeringmentioning
confidence: 99%
“…Such as code search (e.g., [2,24,31,39]), clone detection (e.g., [7,18,19,64,67]), program repair (e.g,. [10,45,60,66]), document (such as API and questions/answers/tags) recommendation (e.g., [22,25,26,55,63,65,69,70,76]).…”
Section: Machine/deep Learning On Software Engineeringmentioning
confidence: 99%
“…In the recent years, several studies have been done to analyze posts on SO, which include analyzing developers' area of interest based on questions asked [5], analyzing and suggesting tags of the questions [2] [1] [6] [7], identifying difficulties faced by developers [8], identifying trending technological topics [9], and so on. Researchers have classified posts on SO based on the context by manually interviewing software developers.…”
Section: Related Workmentioning
confidence: 99%
“…Insofar as the development in methods of classification is concerned, the research community has progressed from significant manual studies to automating them using machine learning algorithms and NLP techniques. Contemporary tools such as EnTAGREC++ [6], TagCombine [7] have been developed to provide tag suggestions to users when they post questions on SO. These tools…”
Section: Related Workmentioning
confidence: 99%
“…The outcome revealed that the developed model gives 65 percent correct results in a situation where one tag prediction is needed on average. Besides, the work of Xia et al (2013) and Wang, Xia and Lo (2015) also focused on developing a technique called TagCombine, aimed to propose tags automatically which examine objects in software information websites. The output of the conducted experiments revealed that TagCombine outperformed the available tag recommendation methods.…”
Section: Mining So For Software Developmentmentioning
confidence: 99%